Antiresorptive agents' bone‐protective and adjuvant effects in postmenopausal women with early breast cancer. Issue 6 (25th January 2019) - Chukir, Tariq; Liu, Yi; Farooki, Azeez
Abstract: Potent antiresorptive drugs (bisphosphonate and denosumab) are often used to protect bone health in postmenopausal breast cancer patients. In addition, clinical trials have shown that these drugs increase disease‐free survival, though the mechanism of adjuvant benefit is largely unknown. Here we review the bone health and adjuvant data for both classes of antiresorptive drugs and highlight differences in their pharmacology. Inhibition of bone resorption is vitally important to protect against osteoporotic fractures, and may also contribute to adjuvant survival benefits by making the bone microenvironment less amenable to breast cancer metastasis. After a course of therapy, stoppage of bisphosphonates yields a persistent antiresorptive effect, whereas discontinuation of denosumab causes a rebound increase in bone resorption markers and a loss of bone mineral density to baseline levels. Whether the potential adjuvant benefits of denosumab are also rapidly lost after drug discontinuation deserves further investigation.